Giant Cell Arteritis: A review of current knowledge and new biological treatment options - Cygnarowicz, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction and objective Giant cell arteritis (GCA) is the most common primary systemic vasculitis in Europe. It mainly affects individuals over the age of fifty, its incidence increases with age. The most common clinical manifestation is bilateral headache accompanied by systemic symptoms. The disease may be associated with serious complications, such as permanent vision loss, stroke or rupture of aortic aneurysm. The aim of this study is to discuss the current knowledge about giant cell arteritis and new possibilities of biological treatment. Review methods To prepare this review, PubMed and Google Scholar databases were used, searching the following terms: “giant cell arteritis,” “temporal arteritis,” “giant cell arteritis biological treatment,” “giant cell arteritis biological therapy,” “giant cell arteritis treatment,” “giant cell arteritis epidemiology.” The search results were limited to publications from 2007 to 2024, as well as key studies from earlier years, including original papers and randomized, double-blind, placebo-controlled studies. Brief description of the state of knowledge The pathogenesis of GCA remains unclear. Since inflammatory factors appear to play an important role, new therapeutic strategies are aimed in direction to interfere these pathways. Setting a diagnosis of GCA requires imaging studies or a temporal artery biopsy. The results of current treatment with high doses of glucocorticoids are unsatisfying, which has led to ongoing research into new therapeutic options. Summary Early diagnosis and initiation of treatment are crucial for preventing occurrence of complications. Although the current treatment regimen is effective, it leads to many side effects and does not prevent relapses. This highlights the need to better understand the pathomechanism of the disease to develop more precise therapeutic strategies, including biological treatment.